Steel and steelworkers : race and class struggle in twentieth-century Pittsburgh - Hinshaw, John H., 1963- (SUNY series in American labor history., 2002)
Hinshaw (history, Lebanon Valley College) explores the competing efforts of unions, rank and file workers, government, and the steel bosses to define and control the political and social realities of Pittsburgh from the late 1800s to the year 2000. Of particular importance to the discussion is the struggle of African-American workers to achieve civil rights (both on the job and in private life) and to achieve equal power in the unions. Similar weight is given to consideration of competing efforts of communists and anti-communists within the unions to shape the struggle. Annotation copyrighted by Book News, Inc., Portland, OR.